2007
DOI: 10.1038/sj.bmt.1705811
|View full text |Cite
|
Sign up to set email alerts
|

Elevated lactate dehydrogenase is an adverse predictor of outcome in HLA-matched sibling bone marrow transplant for acute myelogenous leukemia

Abstract: Prognostic factors for survival following allogeneic BMT for AML include age, disease status and cytogenetic risk classification. Lactate dehydrogenase (LDH) levels have not been studied as a potential risk factor. We reviewed our experience with BMT for AML and included LDH at the time of admission in an analysis of prognostic factors for survival. We found that LDH 4330 U/l (1.5 times the upper limit of normal at our institution), older age, active disease, peripheral stem cell graft and male-to-male transpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…High lactate dehydrogenase activity was correlated with chemotherapy resistance, less sensitivity to drug, hence short overall survival period and shorter disease free survival period as compared to low lactate dehydrogenase activity group [25].…”
Section: Discussionmentioning
confidence: 90%
“…High lactate dehydrogenase activity was correlated with chemotherapy resistance, less sensitivity to drug, hence short overall survival period and shorter disease free survival period as compared to low lactate dehydrogenase activity group [25].…”
Section: Discussionmentioning
confidence: 90%
“…This registry study proved a significant correlation of serum LDH levels with OS, RFS and CRR in patients with metastasized seminoma. Elevated LDH levels were already associated with poorer outcomes including several solid tumor and hematologic malignancies [18][19][20][21][22] but the value of LDH as a prognostic marker for seminoma patients remained unclear. To find new categories that significantly correlate with outcome, our analysis investigates LDH levels and other patient characteristics as potential prognostic markers, hypothesizing that LDH inversely correlates with outcome in seminoma patients as well.…”
Section: Discussionmentioning
confidence: 99%
“…GVHD predisposes graft recipients to the development of AIHA. Data have also shown that high LD activity independently predicts poor prognosis following allogenic bone marrow transplant for AML [25]. A few cases of congenital absence of haptoglobin have been described especially among Blacks of West African origin (Nigeria, Cameroon) where there is a prevalence of approximately 30% [20].…”
Section: Discussionmentioning
confidence: 99%